(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2018)
The proposed article analyzes one of the methods of applied psychoanalytic interpretation of artistic texts – Jungian, aimed at revealing in the work of the effects of the unconscious, conscious (mature) "I" and the collective unconscious in the form of archetypes. Applying the analytical psychology of K.-G. Young, an attempt was made to archetype study of the Bukovinian narrative of Maria Matios (on the material of the novel "Sweet Darusia"). It is proved that the basis of psychotraumatic experience of Daryna Ilashchuk and its psychological dependence on the events of the past are the rejection of the "I", suppression of the archetypes "Shadow and Person," the error of the processes of individuality and self.